Provision of medicines care provided in municipal health care institutions in the Moscow region in stationary conditions (2012 - 2014 years) - M. G. Malaev (Izdatelstvo OKI, 2018)
Difficult economic situation in the country requires the government decision urgently measures aimed at improving the efficient use of available financial and material resources, including through the development of domestic production of medicines and increasing the share of the cost of their acquisition in the implementation of government programs. The study of purchases of medicines by health care organizations in Moscow Region over the past 3 years (2012 - 9 mon